Age-specific cost of first reproduction in female southern elephant seals - Desprez, M; Harcourt, R; Mark Hindell; Cubaynes, S; Gimenez, O; Clive McMahon (2014)
When to commence breeding is a crucial life-history decision that may be the most important determinant of an individual's lifetime reproductive output and can have major consequences on population dynamics. The age at which individuals first reproduce is an important factor influencing the intensity of potential costs (e.g. reduced survival) involved in the first breeding event. However, quantifying age-related variation in the cost of first reproduction in wild animals remains challenging because of the difficulty in reliably recording the first breeding event. Here, using a multi-event capture–recapture model that accounts for both imperfect detection and uncertainty in the breeding status on an 18-year dataset involving 6637 individuals, we estimated age and state-specific survival of female elephant seals ( Mirounga leonina ) in the declining Macquarie Island population. We detected a clear cost of first reproduction on survival. This cost was higher for both younger first-time breeders and older first-time breeders compared with females recruiting at age four, the overall mean age at first reproduction. Neither earlier primiparity nor delaying primiparity appear to confer any evolutionary advantage, rather the optimal strategy seems to be to start breeding at a single age, 4 years.